Experimental Study to Establish Compressive and Flexural Strength of High Performance Concrete (HPC) with Addition of Treated Cocos Nucifera Fiber - Azree Othuman Mydin, Md; Mohamad, Noridah; Nasrun Mohd Nawi, Mohd; Aziz Abdul Samad, Abdul; Johari, Izwan (International Journal of Engineering and Technology, 2018)
This paper focuses on laboratory investigation to establish the mechanical properties of High Performance Concrete (HPC) of grade M60 with addition of treated cocos nucifera fiber (CNF) together with silica fume (SF) and pulverised fuel ash (PFA). There are 3 diverse mix designs of CNF strengthened concrete (CNFRC) were prepared accordingly. Foremost CNFRC deprived of any additive, subsequent CNFRC made by 10% replacement of cement mass with PFA, followed by arrangement of 10% of ordinary cement (by weight) was supplanted with SF. For respective mix design, CNF was included in the mix 0.5% from the total volume. Test results had indicated that by adding CNF lead to 3% decrease in axial compressive strength of the HPC which was due to dropping the quality of compaction. Through the axial compression test performed, the strength of CNFRC PFAC was about 8% greater associated to the control specimen as PFA by means of its globular element form. Moreover, the inclusion of fiber in the mix had develops the strength under flexure load of CNFRC, CNFRC SFC, CNFRC PFAC by about 10%, 8%, and 25% correspondingly. Â Â Â